Augmented reality using range images - Schütz, Christian L.; Hügli, Heinz (My University, 1997)
This paper proposes range imaging as a means to improve object registration in an augmented reality environment. The addressed problem deals with virtual world construction from complex scenes using object models. During reconstruction, the scene view is augmented by superimposing virtual object representations from a model database. The main difficulty consists in the precise registration of a virtual object and its counterpart in the real scene. The presented approach solves this problem by matching geometric shapes obtained from range imaging. This geometric matching snaps the roughly placed object model onto its real world counterpart and permits the user to update the virtual world with the recognized model. We present a virtual world construction system currently under development that allows the registration of objects present in a scene by combined use of user interaction and automatic geometric matching based on range images. Potential applications are teleoperation of complex assembly tasks and world construction for mobile robotics.
Keywords: augmented reality; range imaging; geometric matching; virtual world construction